THE ACCEPTABLE STRATEGIES FOR NEW PRODUCT DEVELOPEMENT IN SERBIAN SMALL-SCALE MANUFACTURING ENTERPRISES - Vorkapić, Miloš; Ćoćkalo, Dragan; Đorđević, Dejan (Journal of Applied Engineering Science, 2016)
The research results relating to the new product development are represented in this paper. The importance of market pull strategy is described too. Market pull strategy is reflected in the enterprise cooperation with customers from idea concept to final product, which includes R&D activities. Customers appear as external sources of ideas, but instead of them the main sources of ideas are competitors and fairs. Also, marketing activities in SMEs are very limited. In comparison to the neighboring countries Serbia does not have inferior position. For the new product development in Serbian enterprises with small-scale production, the paper proposes two strategies: "open Innovation" and "innovative network". Open innovations are important because of the close cooperation between companies and external knowledge sources, while innovative networks strategy has its advantages in creating business cooperation with subcontractors in the use of ideas and knowledge sources. Limitations of this study are: very poor response rate, geographical limitation and lack of a specific homogeneous group of samples in the analysis of certain parameters.